Shepherd on Causal Necessity and Human Agency - Louise Daoust (Journal of Modern Philosophy, 2022)
Shepherd defends an account of the universe founded on two causal principles: that effects necessarily have causes, and that like causes have like effects. Folding mind into the class of natural phenomena governed by these principles, Shepherd naturalizes the mind, but in doing so she sets herself the challenge of explaining how, within a deterministic universe, agents can be necessary causes of their own actions. With special attention to Shepherd’s resistance to materialism and to any reduction of the mental, the paper argues that we can read Shepherd as leveraging her original theory of causation to develop a distinctive compatibilist view of the psychology of intention, one that makes agents the necessary causal sources of their own actions.